Red Hat Enterprise Linux 6 Administration : Real World Skills for Red Hat Administrators - Vugt, Sander van (Serious skills., 2013)
The definitive guide to administering a Red Hat Enterprise Linux 6 networkLinux professionals who need a go-to guide on version 6 of Red Hat Enterprise Linux (RHEL) will find what they need in this comprehensive Sybex book. It covers RHEL administration in detail, including how to set up and manage web and mail services, use RHEL in enterprise environments, secure it, optimize storage, configure for virtualization and high availability, and much more. It also provides a great study aid for those preparing for either the RHCSA or RHCE certification exam. Red Hat is the Linux market leader, and Red Hat administrators are in demandThis Sybex guide is a comprehensive resource on Red Hat Enterprise Linux administration and useful for those preparing for one of the Red Hat certification examsCovers setting up and managing web and mail services, using RHEL in enterprise environments, securing RHEL, and optimizing storage to fit your environmentExplores advanced RHEL configurations, including virtualization and high availabilityRed Hat Enterprise Linux 6 Administration is the guide Linux professionals and Red Hat administrators need to stay current on the newest version.